Enhancement Wear Resistance of Carbon Dual Phase Steel by Cryogenic Treatment - Hussein, Abbas A.; Muhammad, Hussein B. (Nahrain University College of Engineering Journal, 2014)
Dual phase steels containing three different amounts of martensite 21, 37 and 87 Vol. Pct. have been made from carbon steels containing 0.12, 0.33 and 0.43 wt. pct. Carbon respectively. Intercritical annealing treatment at 760 ºC was employed, followed by quenching in Brine. Cryogenic treatment was carried out using liquid nitrogen. Dry sliding wear tests have been conducted on Dual phase (DP) steels before and after cryogenic treatment, using a pin-on disk machine under load 25 N and at a constant sliding velocity 1.74 m/s, for 10 min. at room temperature. Wear properties have been found to improve with the increase in martensite volume fraction in dual phase steels, also, it was observed that, after cryogenic treatment the wear resistance of dual phase steel has improved.